Integration of therapeutic cargo into the human genome with programmable type V-K CAST - Jason Liu; Daniela S. Aliaga Goltsman; Lisa M. Alexander; Khak Khak Khayi; Jennifer H. Hong; Drew T. Dunham; Christine A. Romano; Morayma M. Temoche-Diaz; Shailaja Chadha; Rodrigo Fregoso Ocampo; Jennifer Oki-O’Connell; Owen P. Janson; et al. (Nature Communications)
Abstract CRISPR-associated (Cas) transposases (CAST) are RNA-guided systems capable of programmable integration of large segments of DNA without creating double-strand breaks. Engineered Cascade CAST function in human cells but are challenging to deploy due to the complexity of the targeting components. Unlike Cascade, which require three Cas proteins, type V-K CAST require a single Cas12k effector for targeting. Here, we show that compact type V-K CAST from uncultivated microbes are repurposable for programmable DNA integration into the genome of human cells. Engineering for nuclear localization and function enables integration of a therapeutically relevant transgene at a safe-harbor site in multiple human cell types. Notably, off-targets are rare events reproducibly found in specific genomic regions. These CAST advancements are expected to accelerate applications of genome editing to therapeutic development, biotechnology, and synthetic biology.